PENINGKATAN LITERASI DIGITAL DALAM RANGKA MEMUDAHKAN AKSES INFORMASI BAGI MASYARAKAT DI WILAYAH TEGAL - Prasetyo Tulodo, Rizki; Sofyan, Ali; Indah Fitria, Ria; Mahabba Haeta, Sofa (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2024)
The rapid development of technology and information, particularly the use of the internet, has driven changes in various fields, including digital literacy. However, literacy levels in some regions of Indonesia, such as Tegal, Kabupaten Tegal, remain low. This situation is caused by several factors, including the lack of support from the Tegal Village Government in promoting a literacy culture, both through policies and the provision of infrastructure such as village libraries. Additionally, the community perceives literacy as important only for children and teenagers who are pursuing education, rather than a part of everyday culture. The lack of socialization and outreach by academics and educational institutions to the community also exacerbates this condition. In fact, digital literacy is an essential skill for accessing, understanding, and using information wisely in the digital era. Therefore, raising awareness of the importance of digital literacy through more inclusive policies, the provision of infrastructure, and the active role of the community and academics is key to improving literacy in the Tegal region